Capturing sequence variation among flowering-time regulatory gene homologs in the allopolyploid crop species Brassica napus - Schiessl, Sarah; Samans, Birgit; Hüttel, Bruno; Reinhard, Richard; Snowdon, Rod J. (Frontiers in Plant Science, 2014)
Flowering, the transition from the vegetative to the generative phase, is a decisive time point in the lifecycle of a plant. Flowering is controlled by a complex network of transcription factors, photoreceptors, enzymes and miRNAs. In recent years, several studies gave rise to the hypothesis that this network is also strongly involved in the regulation of other important lifecycle processes ranging from germination and seed development through to fundamental developmental and yield-related traits. In the allopolyploid crop species Brassica napus, (genome AACC), homoeologous copies of flowering time regulatory genes are implicated in major phenological variation within the species, however the extent and control of intraspecific and intergenomic variation among flowering-time regulators is still unclear. To investigate differences among B. napus morphotypes in relation to flowering-time gene variation, we performed targeted deep sequencing of 29 regulatory flowering-time genes in four genetically and phenologically diverse B. napus accessions. The genotype panel included a winter-type oilseed rape, a winter fodder rape, a spring-type oilseed rape (all B. napus ssp. napus) and a swede (B. napus ssp. napobrassica), which show extreme differences in winter-hardiness, vernalization requirement and flowering behaviour. A broad range of genetic variation was detected in the targeted genes for the different morphotypes, including non-synonymous SNPs, copy number variation and presence-absence variation. The results suggest that this broad variation in vernalisation, clock and signaling genes could be a key driver of morphological differentiation for flowering-related traits in this recent allopolyploid crop species.